Pengaruh Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Studi Pada PT Swadaya Graha (Semen Indonesia Group) Gresik - Mufarokhah, Nur (Akutansi Bisnis & Manajemen ( ABM ), 2019)
Leadership and motivation are important factors in the organization. This is expected to improve employee performance in the company. The purpose of this research was to determine the effect of leadership and motivation on employee performance. The results of the research show that there is a positive influence between leadership and motivation on employee performance. Data collection methods used by distributing questionnaires with the population in this research were PT Swadaya Graha Gresik as many as 98 respondents.